Oral language comprehension interventions in 1–8-year-old children with language disorders or difficulties: A systematic scoping review. (August 2020) - Tarvainen, Sirpa; Stolt, Suvi; Launonen, Kaisa
Background and aims: The most severe problems in language manifest as difficulties in comprehending oral language. These difficulties are persistent and expose individuals to several risk factors. There is a lack of intervention research in the area of oral language comprehension, and no reviews have focused solely on oral language comprehension interventions in young children. The aim of this review was to identify interventions targeting oral language comprehension in children 8 years or younger with language disorders or difficulties. The review also examined the possible intervention foci, efficacy, and level of evidence of these interventions. Methods: A systematic scoping review of eight databases was carried out. Twenty of 2399 articles met the inclusion criteria and a further six articles were identified through reference lists of sourced articles. These 26 articles described 25 studies. Altogether 2460 children aged 1–8 years participated in the 25 studies. The data from these studies were extracted and analysed, and the intervention foci, efficacy, and level of evidence were evaluated. Main contribution: The reviewed interventions focused on three aspects: modifying the communicative environment of the child; targeting aspects of the child's language; or targeting the child's language processing. Of the included studies, 80% indicated positive effects on participants' oral language comprehension. The level of evidence of the included studies varied. With few exceptions, researchers and practitioners can have moderate confidence in the results of the included studies indicating that it is possible to ameliorate difficulties in oral language comprehension. Conclusions: This review summarises the existing evidence on oral language comprehension interventions in young children with language disorders or difficulties. The evidence base is still limited, and more research is urgently needed. The results suggest that though not all interventions seem to provide desired outcomes, there are several interventions indicating efficacy to target problems in oral language comprehension in 1–8-year-old children with language disorders or difficulties. A careful choice of therapy technique and collaboration with people in the child's environment is required to maximize outcomes. Implications: The results suggest that young children's oral language comprehension skills can be improved by guiding parents and clinicians in their communication strategies, and by clinician-implemented interventions targeting aspects of the child's language. The research on interventions targeting children's language processing is limited, and the results mixed. The present study provides information on different oral language comprehension interventions and their outcomes. The findings are readily applicable for clinical use.